2011
DOI: 10.1093/jinfdis/jiq064
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Tuberculosis: A Risk Factor for Mother-to-Child Transmission of Human Immunodeficiency Virus

Abstract: Maternal TB is associated with increased MTCT of HIV. Prevention of TB among HIV-infected mothers should be a high priority for communities with significant HIV/TB burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…The most common organisms associated with pneumonia, Streptococcus and Haemophilus, occur in HIV patients at similar rates to those in the non-HIV population. 45 An estimated 30% of HIV-infected persons worldwide have latent MTB. Methicillin-resistant Staphylococcus aureus is associated with a severe, necrotizing pneumonia and increased mortality in HIV-positive patients.…”
Section: Bacterial Ois and Pneumoniamentioning
confidence: 99%
See 1 more Smart Citation
“…The most common organisms associated with pneumonia, Streptococcus and Haemophilus, occur in HIV patients at similar rates to those in the non-HIV population. 45 An estimated 30% of HIV-infected persons worldwide have latent MTB. Methicillin-resistant Staphylococcus aureus is associated with a severe, necrotizing pneumonia and increased mortality in HIV-positive patients.…”
Section: Bacterial Ois and Pneumoniamentioning
confidence: 99%
“…Concomitant treatment of HIV and MTB causes concern for drug interactions, overlapping drug toxicities, and IRIS. 45 HIV-positive pregnant women should be screened and treated for latent MTB. Delaying ARV therapy 4 to 12 weeks after MTB treatment initiation does not impact overall survival.…”
Section: Bacterial Ois and Pneumoniamentioning
confidence: 99%
“…Studies have associated several maternal HIV coinfections (including cytomegalovirus infection, hepatitis C virus infection, active tuberculosis and malaria) with adverse pregnancy and infant health outcomes, and maternal malaria and tuberculosis coinfections are established risk factors for MTCT of HIV and infant mortality . In contrast, data linking maternal HIV/HBV coinfection to adverse pregnancy outcomes such as preterm labour and low birth weight are inconclusive , and the impact of maternal HIV/HBV coinfection on MTCT of HIV and infant mortality remains unclear . Definitive studies to establish the role of maternal HIV/HBV coinfection in HBV‐endemic RLSs are needed, and their findings may result in the prioritizing of changes to local standard of care practices, including routine antepartum screening for HBV in HIV‐infected women and timely vaccination/treatment of HIV/HBV‐coinfected women and their exposed infants.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 TB has also been associated with increased risk of HIV transmission from mother to child. 7 In a meta-analysis of TB symptom screening algorithms coordinated by World Health Organization (WHO), the best performing rule was a 4-symptom screen using one of any of the following: cough in the last 24 hours, fever, night sweats, and weight loss. This 4-symptom screen rule had a sensitivity of 90.1% in a clinic setting and negative predictive value of 98.3%, assuming TB prevalence of 5% among people living with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…CD4 cell count (greater or less than 200 cells/mL) had little impact on the sensitivity or specificity of this symptom screen. [7][8][9][10] The WHO guidelines thus recommend screening for TB using the presence of cough of any duration, fever, night sweats, and weight loss, and collecting sputum for testing from symptomatic persons with any of the symptoms above. 8 Several studies have demonstrated the efficacy of active case finding (ACF) for identification of active TB enabling initiation of appropriate medical therapy, and provision of isoniazid preventive therapy (IPT) to prevent TB.…”
Section: Introductionmentioning
confidence: 99%